National and Cultural Features of Zoomorphic Systems (Texas Journal of Philology, Culture and History, 2023)
This article analyzes the zoomorphic of the Uzbek and German languages and their national, cultural characteristics. The use of zoomorphism peculiar to the culture and social lifestyle of the compared languages is given. The features inherent in animal zoomorphic images, which served as the basis for the creation of the studied phraseological units, are revealed by comparative analysis.